Case studies: teaching mathematics in a school of management - Pérez, Diego Alejandro; Jaramillo, Diana Victoria; Asbahr, Flávia (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Our aim is to show the organizational process of teaching of three math teachers in a management university institution, based on the collective creation of case studies. The dialectical method provided elements to understand this process. On the basis of collective work, the teachers made a case about supply and demand and presented a mathematical understanding to contribute to the analysis and solution of business problems. The theoretical foundation of the research is the historical-cultural theory. In this context, we understand the organization of teaching as the object of the teacher’s activity, and case studies as teaching methodologies. Case maps, semi-structured interviews, audios, videos, ideograms, and concept maps were used as instruments of production of records and data. We analyzed that the writing process by the teachers was permeated by an intention of creating a particular way of showing mathematical knowledge, from their own needs,experiences and expertise.